2020
DOI: 10.1111/bjet.13007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a concept mapping‐based problem‐posing approach on students’ learning achievements and critical thinking tendency: An application in Classical Chinese learning contexts

Abstract: In language courses, it is important to foster students’ systematic thinking and to develop their competence to express, appreciate, criticize and reflect, in particular in such courses as classical Chinese, which aim to develop students’ cultural and literature knowledge. Problem posing is a promising strategy to achieve this objective. However, without sufficient supports, students could feel frustrated since problem posing is a challenging task, in particular for young students. In this study, a fill‐in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 62 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…A concept map is a visual organizer of knowledge that helps students enrich their understanding of a particular domain ( Novak and Gowin, 1984 ). CM was found useful in enhancing 10th-grade students’ scientific inquiry course performance ( Huang et al, 2022 ); improving ninth-grade students’ learning achievement ( Li et al, 2021 ); affecting children’s learning achievement, critical thinking, and learning attitude ( Liang et al, 2021 ); enhancing fifth graders’ (especially those with higher levels of critical thinking tendency) learning performance ( Hwang et al, 2021a ); and in improving eighth-grade students’ learning achievement, critical thinking tendency and problem-posing quality ( Hwang et al, 2021b ). A recently published systematic review on the roles, applications and trends of concept map-supported learning ( Chang et al, 2022 ) showed the benefits of using concept maps to facilitate knowledge construction in collaborative learning and improve learning achievement and motivation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A concept map is a visual organizer of knowledge that helps students enrich their understanding of a particular domain ( Novak and Gowin, 1984 ). CM was found useful in enhancing 10th-grade students’ scientific inquiry course performance ( Huang et al, 2022 ); improving ninth-grade students’ learning achievement ( Li et al, 2021 ); affecting children’s learning achievement, critical thinking, and learning attitude ( Liang et al, 2021 ); enhancing fifth graders’ (especially those with higher levels of critical thinking tendency) learning performance ( Hwang et al, 2021a ); and in improving eighth-grade students’ learning achievement, critical thinking tendency and problem-posing quality ( Hwang et al, 2021b ). A recently published systematic review on the roles, applications and trends of concept map-supported learning ( Chang et al, 2022 ) showed the benefits of using concept maps to facilitate knowledge construction in collaborative learning and improve learning achievement and motivation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research on concept maps as a cognitive tool mainly focuses on the impact of concept maps on student learning. For example, Hwang et al (2020)found that the problem-producing method based on concept maps can improve students' academic performance, critical thinking tendency, and the quality of problem-producing. When the concept map is used as an evaluation tool, it usually includes the evaluation of the concept map and the evaluation of the students' knowledge construction through the concept map.…”
Section: The Role Of Concept Mapping In Instructionmentioning
confidence: 99%
“…They can help students focus on thinking tasks with a high cognitive load by reducing their low-level cognitive load (Jonassen, 1992;Lajoie and Derry, 1993). Many studies have shown that concept maps can promote students' critical thinking and other higher-order thinking skills (Hwang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to improve the achievement of students' essay writing achievement in the English Language Education Study Program throughout the country, mind maps are necessary and very relevant to the current education. In addition, the use of mind maps can help improve student achievement in the English Language subjects (Aljaser, 2017;Hwang, Huang, Wang, and Zhu, 2021;Fang, He, Hwang, Zhu, Bian & Fu, 2022). Writing is a subject assessed language skills teaching.…”
Section: Introductionmentioning
confidence: 99%